A Study on the Factors Influencing Social Entrepreneurial Intention Among Undergraduates - Chan, Wai Hoong; Qureshi, Zuhaib Hassan; Sulaiman, Sajilan; Al Halbusi, Hussam (2019)
This paper provides an insight on factors affecting the social entrepreneurial intention among undergraduates in Malaysia. Specifically, this paper emphasizes on external factors in influencing the Malaysian undergraduates' intention on becoming a social entrepreneur. The Theory of Planned Behaviour (TPB) was used as an underpinning theory to support the proposed conceptual model. Quantitative research method was used in this study. The sample consisted of 600 respondents, which comprises of undergraduates of Malaysian private universities. Likert scale questionnaire were distributed to the respondents to complete. The collected data were analysed using SPSS software and Partial Least Squares Structural Equation Modelling (PLS-SEM). Based on the research findings within this paper, some of the external factors greatly affect an undergraduate's intention on becoming a social entrepreneur in the future. The stated external factors are opportunity recognition and access to finance. However, the other factor, social capital, was found that it did not influence an undergraduate's intention to become a social entrepreneur.